Implementation of RFID for Verification of PC Usage in the UMSIDA’s Electrical Engineering Laboratory Based on the Internet of Things - Muhammad Drajad Kuncoro Aji; Jamaaluddin Jamaaluddin; Izza Anshory; Akhmad Ahfas (Procedia of Engineering and Life Science, 2021)
Every day visitors to the UMSIDA electrical engineering laboratory have different goals. The main function of the laboratory is as a practicum for electrical engineering students and is also used to work on coursework. This study aims to control the use of laboratory PCs using Internet of Things-based RFID card verification. The application of RFID connected to the Wemos D1 Mini is expected to be able to reduce unexpected actions such as theft and hacking of data on the PC. The PC will be installed with an RFID reader to verify the RFID card as the initial stage of PC use. The results of the research trials showed that by bringing the RFID card from 0 cm to 2.5 cm closer to the RFID reader, the RFID card was successfully verified effectively. When the RFID card is successfully verified by the RFID reader, the PC will automatically turn on, the verification results will be displayed on the 16 x 2 LCD and android smartphone so that they can monitor every time and get an android notification that sends information that the verification process was successful and the PC is on. Laboratory PCs are safer from unwanted use by using RFID technology that is connected to the Wemos D1 Mini for monitoring and controlling via a smartphone remotely in real-time because before using a PC, it must go through a verification process.